My cherie - Easton, Sheena; Diante, Denny; MCA Records (California : MCA Records, 1995)
Contains four versions of the single taken from the album My Cherie.
CD 1 - Radio edit/ (4:02) -- AC edit / (3:52) -- AC full version / (4:10) -- LP version / (4:20).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English